2012
DOI: 10.2478/v10096-012-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hydrocarbon potential of Jurassic and Cretaceous source rocks in the Tarnogród-Stryi area (SE Poland and W Ukraine)

Abstract: Abstract:The Jurassic/Cretaceous stratigraphic complex forming a part of the sedimentary cover of both the eastern Małopolska Block and the adjacent Łysogóry-Radom Block in the Polish part as well as the Rava Rus'ka and the Kokhanivka Zones in the Ukrainian part of the basement of the Carpathian Foredeep were studied with geochemical methods in order to evaluate the possibility of hydrocarbon generation. In the Polish part of the study area, the Mesozoic strata were characterized on the basis of the analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…In the Mesozoic profile in the southeastern part of Poland only the Middle Jurassic strata show rock complexes that meet the quantitative criteria of source rocks (Kosakowski et al 2012b). The geochemical analysis performed in those strata revealed that the Triassic, Upper Jurassic and Cretaceous strata present generally very low TOC and hydrocarbon (S 1 +S 2 ) contents, and low thermal maturity of organic matter additionally reduced their source rock potential.…”
Section: Modelling Of Maturation and Generation Historyresults And DImentioning
confidence: 99%
See 3 more Smart Citations
“…In the Mesozoic profile in the southeastern part of Poland only the Middle Jurassic strata show rock complexes that meet the quantitative criteria of source rocks (Kosakowski et al 2012b). The geochemical analysis performed in those strata revealed that the Triassic, Upper Jurassic and Cretaceous strata present generally very low TOC and hydrocarbon (S 1 +S 2 ) contents, and low thermal maturity of organic matter additionally reduced their source rock potential.…”
Section: Modelling Of Maturation and Generation Historyresults And DImentioning
confidence: 99%
“…The organic matter is immature, or mature in the early phase of the "oil window". The maturity of kerogen increases towards to Outer Carpathians (Kosakowski et al 2012b). …”
Section: Modelling Of Maturation and Generation Historyresults And DImentioning
confidence: 99%
See 2 more Smart Citations
“…Al though the Up per Ju ras sic strata in the study area are lean in or ganic mat ter, in the Ukrai nian part of the Me so zoic base ment (Kosakowski et al, 2012b) and the Pol ish Low lands (Wiêc³aw, 2016) their hy dro car bon po ten tial is lo cally very high and the dom i nant oil-prone Type-II kerogen is ca pa ble of pe troleum gen er a tion. Wiêc³aw (2011) and Wiêc³aw et al (2012b) con sid ered them as most prob a bly the source rock of heavy oils ac cu mu lated in the Up per Ju ras sic car bon ate de pos its in the Pol ish-Ukrai nian bor der area (Lubaczów, Kokhanivka and Orchovichi de pos its).…”
Section: Discussionmentioning
confidence: 99%